2018
DOI: 10.1016/j.jgo.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Use of frailty to predict survival in elderly patients with early stage non-small-cell lung cancer treated with stereotactic body radiation therapy

Abstract: Frailty is associated with lower OS in older patients with early stage NSCLC treated with SBRT, yet frail patients survived a median 2.5years, and were more likely to die of causes unrelated to the primary lung cancer, suggesting SBRT should be considered even in older patients deemed unfit for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…In agreement with a previous study in SBRT-treated NSCLC patients by Franco et al, our CSS findings suggest, though not statistically significant, that the majority of these patients died of other causes than lung cancer, and the frail G-8 and HGST group was at the highest risk [41]. In our study, none of the frail G-8 and HGST combination group patients died of lung cancer, demonstrating the importance of a future focus on optimizing age-related comorbidities in older SBRT-treated patients with localized NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with a previous study in SBRT-treated NSCLC patients by Franco et al, our CSS findings suggest, though not statistically significant, that the majority of these patients died of other causes than lung cancer, and the frail G-8 and HGST group was at the highest risk [41]. In our study, none of the frail G-8 and HGST combination group patients died of lung cancer, demonstrating the importance of a future focus on optimizing age-related comorbidities in older SBRT-treated patients with localized NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…From the early stage to the late stage of lung cancer, the proportion of frailty increased (22). However, there was no significant difference in the incidence of frailty between stage 1A and 1B/2A patients (14). Franco et al (14) found that overall stage did not influence the survival of patients by univariate analysis (1B/2A vs. 1A, P = 0.46).…”
Section: Discussionmentioning
confidence: 97%
“…All of these studies were hospital-based registry cohort studies. A total of 3,921 lung cancer patients involved in these seven studies received different treatments, surgery in two (17,21), radiotherapy in two (14,15), chemotherapy in two (22), unreported in one. Three of these included studies classified patients as prefrail and frail, and one classified patients as mild, moderate and severe frailty.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…To some extent, it is reasonable to regard FI-LAB as a risk indicator of poor outcomes after chemotherapy. Simply including frailty assessment in the risk assessment before chemotherapy may help to facilitate appropriate treatment planning for older patients with lung cancer 2022…”
Section: Discussionmentioning
confidence: 99%